ProKlim: Institutional Data Inventory Assistance at Site Level - Khuriyatul husna; Alexsander Yandra (Universitas Lancang Kuning, 2023)
The Climate Village Program (ProKlim) is a national movement for community-based climate change control and aims to build a climate-resilient society. The determination of the area to be ProKlim is determined by the results of the assessment of the National Registry System for Climate Change Control (SRN PPI). The recorded areas make it easier for the Government to collect data regarding the addition of regions that are contributors in the Nationally Determined Contribution (NDC). Various benefits can be achieved by regions and communities that are included in the SRN and are nominated. But unfortunately many regions and communities do not know and understand what ProKlim is and its benefits are recorded in the PPI SRN. Therefore, education and assistance activities related to the data inventory needed in the SRN PPI are important to do. The method of implementing service activities is carried out in the form of education related to ProKlim and SRN PPI, Focus Group Discussions (FGD) and assistance in inventorying institutional data. The institutional aspect is the main concern of the service team because it has a weight of 40 percent of the assessment. So that institutional strengthening in terms of knowledge and assistance for managers of various ProKlim activities is very much needed. The success of climate change